The Concept of Russia in Nikolai Gogol’s Poem, “Dead Souls” - Kiklewicz, Aleksander (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The article presents an analysis of the concept of “Russia” in Nikolai Gogol’s poem “Dead Souls”. The subject of linguistic analysis was 118 text fragments (simple and complex sentences), including the nouns Russia and Rus and the adjective Russian, which were examined from the point of view of the information about Russia contained in them. To analyse the language material, a facet technique was used, which made it possible to present the content of the concept of Russia at several levels: 1) categories of characteristics (facets); 2) characteristics of two types: organic (intrinsic) and axiological, while the article describes in detail the most frequent categories and characteristics. The study was carried out within the framework of linguistic culturalism and is based on the theory of functional semantics, in particular, on such areas as conceptology and imagology.